Sharia Economics and Business Spirit with Noble Morals: Community Service at SDN 2 Muhammadiyah Mamajang - Nur isnaini syaifullah; Siti Walida Mustamin; Winarti. A; Salfa Seti; Sarmila; Khusnul Khatima Asrul; Arifin; Nurul Hilmi; Nurmi; Bayu Irsandy; Esti Qama (www.amertainstitute.com, 2025)
The integration of Islamic economic values into elementary education is essential to cultivate ethical financial behavior and entrepreneurial orientation from an early age. This community service program was designed to enhance students’ understanding of sharia economics and foster a business spirit grounded in noble morals. The program was implemented at SDN 2 Muhammadiyah Mamajang, Makassar, targeting 40 fourth- and fifth-grade students aged 9–11 years. A participatory action research (PAR) approach was applied through interactive learning methods such as storytelling, games, role-play simulations, and reflective discussions. The training modules covered fundamental Islamic economic principles, including the pillars of buying and selling, sharia contracts such as murabahah and salam, and ethical values of honesty, trustworthiness, and accountability in transactions. Data were collected through observation, quizzes, interviews, and documentation, and analyzed thematically to capture cognitive, affective, and behavioral outcomes. The findings revealed significant improvements in students’ conceptual understanding of halal transactions, ethical awareness in economic interactions, and observable behavioral changes such as fair pricing and responsible money handling. Moreover, students demonstrated an emerging entrepreneurial spirit with a spiritual orientation, expressing intentions to engage in small-scale businesses guided by honesty and social responsibility. These results highlight the effectiveness of experiential learning in transmitting Islamic economic values and underscore the potential of community service programs as a medium for character education and sharia economic literacy at the elementary level.